Recurrence: a novel. Book one - Shrayfer, Lilia, author; Ausubel, Ramona, advisor; Levy, E. J., advisor; Yalen, Deborah, committee member; Foskin, Kevin, committee member (Colorado State University. Libraries, 2023)
Inspired by the disappearances of over a dozen Soviet Jews during the refugee crisis between 1979-1989 in Italy, this novel aims to offer a speculative portal into the crises of identity that may have led to such tragedy. Spanning three generations of one Bukharan-Jewish family, from Stalin's purges of the 1930's, to Khruschev's Sovietization campaign, to the Soviet Invasion of Afghanistan, to the above period of statelessness in Europe, the book explores this family's exile through the lens of Eva Kalandarova's gender and sexual identity. What is transmasculinity for transient lives? What does it mean for someone haunted by the sins of their father? In 1941, Russian poet Anna Akhmatova was evacuated to Central Asia, where she and other Russian writers in exile sought to recreate literary life. It is in Central Asia that she wrote—and later burned—her only play of a writer condemned not only by the state, but by her peers. Her contemporaries at the time, such as Nadezhda Mandelstam, write that she saw the future of the Soviet Union. Inspired by her diary entries detailing typhus-induced hallucinations, the novel speculates on the possibility that Akhmatova's relationship with the landscape and its locals may be found in her work. Accordingly, the novel imagines parallel dreams and associations between the Bukharan Jewish families centered in this book and her writing. Similarly, the novel explores Ladispoli as a mirror to the historical anxieties and traumas of the Jews of Rome. I have aimed for a poets' novel; I have aimed for a historical fiction novel, a speculative novel, a trans-national Jewish novel that imagines new Jewish questions. I have aimed to situate my people amidst the Jewish literature that has too long overlooked them, for even in our silence, we have much to say.
Keywords: exile; Jewish; Bukharan; Soviet; historical fiction